Ku modelowi konfrontatywnego badania języka prawosławia i katolicyzmu - Madjieva, Viara (Stylistyka, 2020)
The work presents a preliminary proposal for a model of confrontative study of the language of Orthodoxy and Catholicism. A confrontative study refers to a type of comparison in which the objects being compared are equal, that is, the description of none of them is initial. Equality of the studied objects is achieved with the help of tertium comparationis, understood as an intermediary language, consisting of units of meaning and relations between them (compatibility rules). When comparing language denomination codes, the intermediary language is built at the level of the text – its units are genres that appear in religious texts. At the first stage of comparison, directed from meaning to form, a list of genres in the field of two types of texts is determined: analytically-systematizing and empirical. This division is basic from the point of view of semantics and language form, and thus from the point of view of observation and analysis methods. At this stage, several genres are examined and compared in terms of the concepts and their content that are fundamental to the texts of a given genre, as well as from the point of view of intertextuality essential for religious discourse: references to the Holy Scriptures, Traditions (for example Church Fathers) and dogma. Also at this stage, the processes occurring in the field of the list of genres are investigated: the emergence of new genres and modification of the existing ones. At the second stage, the object of comparison, directed from form to meaning, is the linguistic characteristic of genres in two aspects: the presence and intensity of feature of the biblical language in lexis, morphology, syntax in a given genre, and its own feature of lexis, morphology, and syntax of individual genres. At this stage, processes in the field of form are also taken into account and relate to the linguistic differentiation of the sacred and secular in Orthodoxy and Catholicism.